The Effects of Personality and Management Role on Perceived Values in Business Settings - Reynierse, James H.; Ackerman, Dennis; Fink, Alexis A.; Harker, John B. (2000)
This paper examines the effects ofpersonality variables and functional management role,either entrepreneur, manager in an entrepreneurialfirm, manager in a traditional firm, or small businessowner, on perceived business values. Functionalmanagement role had minimal discernible effects;personality variables differentiated entrepreneursfrom managers and produced many effects for ratings ofbusiness values. Results are discussed in terms ofMBTI and DISC theoretical constructs and theirimplications for entrepreneurship and management.
Keywords: DISC; MBTI; Personality; Management; Entrepreneurship; business values